Fundamentalisme dan Inklusivisme dalam Paradigma Perubahan Keagamaan - Maimun Fuadi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Fundamentalism is a historical phenomenon in the discourse of religious thoughts, in where Islam is included in. The association of fundamentalism to a  group tends to picture the negative impact in its development process. Radicalism,  militant, terrorism, and exclusivism color and are strongly attached to Islamic  fundamentalism. In fact, since its invention, Islam calls for open minded and  inclusivism in practicing the religion teachings. For that, the change of paradigms  particularly in relation with religious understanding – such as Islamic  fundamentalism – is a process that requires bravery, vision, and specially clear  and pure mind in understanding spirit of God’s teachings. These are required by  Islamic fundamentalism to actualize earthly prosperity and peace.